Decision Support System for Selection of Pesticides in Chili Plants Using the MAUT Method - Sukamto, Sukamto; Nugroho, Riki Ario; Nugrah, Randi Andri (ISB Atma Luhur, 2023)
Diseases in chili plants often cause farmers to experience crop failure. Diseases that are often encountered are leaf spot disease, wilt disease, and anthracnose disease caused by fungi. Therefore, farmers are trying to prevent and reduce the disease by using pesticides. The use of pesticides in agriculture plays a role in preventing and reducing diseases in chili plants. Pesticides for chili plants are quite widely spread on the market and have the advantages of each product offered to farmers, so farmers must be more careful and understanding in choosing pesticides to be used in preventing chili plant diseases. For that we need a decision support system (SPK). The purpose of this research is to apply the MAUT method in SPK which can help chili farmers in selecting pesticides. The data used in this study are 10 types of pesticides as an alternative. While the criteria consist of price, classification, number of diseases eradicated, method of action, shelf life, and formulation concentration. Data analysis uses the MAUT method with the steps of forming a decision matrix, normalizing the decision matrix, determining the utility matrix, calculating the final utility, and ranking. The research results obtained for the three best pesticides are Tridex 80 WP, Ziflo 76 WG, and Cabriotop 60 WG.